EFEKTIVITAS PELAKSANAAN SOSIALISASI KEPROTOKOLAN DALAM PELAKSANAAN TUGAS POKOK DAN FUNGSI PEGAWAI - Abbas Abbas; Reza Indarsa Halim (Universitas Bandar Lampung (UBL), 2023)
This study aims to analyze the Socialization of Protocol in the Implementation of Duties, Principles and Functions of Employees in the Protocol section of Lampung Province. The method used in this research is descriptive qualitative research. This research is a study whose main purpose is to describe or explain a situation and conditions that actually occur. Data collection techniques include observation, interviews, and documentation. The sources and types of data used in this research are primary data, which are obtained directly from the field, and secondary data obtained from books, journal articles, and the internet. The results of the research Socialisation in the Implementation of Main Duties and Functions in the Protocol Section of Lampung Province are still not going well, the socialitator has not projected itself to the recipient of socialisation, the message conveyed has been conveyed well, the media used is quite adequate, as the recipient of socialization is sometimes not optimal, the effect or impact of this socialization flow is less clear. What aspects hinder Socialisation in the Implementation of Main Duties and Functions in the Lampung Province Protocol Section, namely between superiors and subordinates, can cause obstacles at any time. This is because leaders and staff are still unable to absorb what is each's responsibility.